Giant Star-Shaped Nitrogen-Doped Nanographenes - Mora-Fuentes, Juan P.; Riaño, Alberto; Cortizo-Lacalle, Diego; Saeki, Akinori; Melle-Franco, Manuel; Mateo-Alonso, Aurelio (Angewandte Chemie International Edition, 2019)
Star-shaped nanographenes (SNGs) are large monodisperse polycyclic aromatic hydrocarbons that are larger than a nanometer and have shown a lot of promise in a wide range of applications including electronics, energy conversion, and sensing. Herein, we report a new family of giant star-shaped N-doped nanographenes with diameters up to 6.5 nm. Furthermore, the high solubility of this SNG family in neutral organic solvents at room temperature allowed a complete structural, optoelectronic, and electrochemical characterisation, which together with charge transport studies illustrate their n-type semiconducting character.
Created from Fastlane, Scopus look-up
Keywords: cloverphenes; nanographenes; polycyclic aromatic hydrocarbons; star-shaped nanographenes; starphenes